Factors of sustainable development of the «Green economy» - Toxambayeva , A.B. (BUKETOV BUSINESS REVIEW, 2017)
In the article a lot of attention is paid to development of the green economy in Republic of Kazakhstan. According to «Strategy-2050» of President N.А. Nazarbayev’s, Kazakhstan will use renewable and alternative energy sources to create 50 % of the electric capacity generated in Kazakhstan. This is just one component of Kazakhstan’s comprehensive initiative to transfer from one of the world’s premier hydrocarbon energy producers to a model «green» economy. In addition to green energy creation, Kazakhstan’s transition also focuses on water resource conservation, agriculture and waste management, and measures aimed at reducing carbon emissions. Therefore holding such an international event like the Expo 2017 will contribute to accelerating transition to sustainable development in the framework of the «green economy». Kazakhstan has chosen the theme «Future Energy» to promote and discover sustainable global energy solutions. It’s one of the largest international meetings are conducted in Central Asia. It will be held during Astana’s 20th-anniversary as the nations’ capital and celebration the emergence of Independent Kazakhstan generally as an energy and communications hub of Europe. Selected theme of Expo 2017 is bright for the host country and will contribute more prosperous of the region. Kazakhstan is located in a unique and beautiful place to spend this exhibition.